POTENSI KELURAHAN FORAMADIAHI UNTUK EKOWISATA: STUDI EKSPLORASI DAYA TARIK DAN STRATEGI PENGEMBANGAN - Adriani Adriani; Siti Nurjannah; Nurfadhilah Arif (Universitas Khairun, 2025)
This study explores the ecotourism potential of Foramadiahi Village, a historic community situated at the southern slopes of Mount Gamalama in Ternate, Indonesia. The research aims to identify and evaluate natural, cultural, and built attractions that can be developed sustainably to enhance local tourism while preserving environmental and cultural heritage. Employing a mixed-methods approach combining qualitative descriptive analysis with quantitative modelling through SWOT (Strengths, Weaknesses, Opportunities, Threats) and Multi-Criteria Decision Analysis (MCDA), the study prioritizes key tourism assets for strategic development. Findings reveal that natural landscapes and cultural heritage sites offer the highest potential, supported by community readiness and economic viability. Meanwhile, infrastructural limitations and promotional challenges present constraints. The research highlights the importance of integrating community participation, cultural preservation, and environmental sustainability in developing ecotourism. Recommendations emphasize strengthening infrastructure, enhancing digital marketing, and conserving indigenous rituals and traditions as integral components of sustainable tourism development. This study contributes to the growing body of knowledge on community-based ecotourism by providing a data-driven framework to guide strategic planning in comparable rural contexts.